Propriedades eletrônicas e topológicas de nanoestruturas de jacutingaítas à base de platina - Castro, Giselle dos Santos (2025)
In this work, we present a study the electronic and topological properties of platinum-based jacutingaite materials using different formalisms. We begin by developing a refined tight binding Hamiltonian for Pt2NX3 materials (N = Zn, Cd, Hg; X = S, Se, Te), designed to accurately describe the low-energy physics of the respective monolayers. We take into account the significant contributions of spin-orbit coupling, which are fundamental for understanding the topological energy gap present in these materials. Through comparisons with density functional theory calculations, the parameters of the tight-binding model were adjusted to accurately reproduce the energy bands near the Fermi level. The interaction between the Pt d orbitals and the s orbitals of metal N determines the energy dispersion within this spectrum. These elements result in interpenetrating kagome and honeycomb lattice structures, which form the structural basis of our model. The Hamiltonian was extended to explore monolayer nanoribbons, with which we demonstrate that the configuration of the dispersion bands of the topological edge states as well as the penetration length of these states are sensitive to the geometric configurations of the edges. Closed zigzag edges or those with one platinum bond (equivalent to a closed zigzag termination composed of X) exhibit a more robust electronic structure from a topological perspective. Furthermore, we investigated the electronic and optical properties and Berry quatities of a system composed of two monolayers of platinum-based jacutingaite — Pt2CdSe3/Pt2HgSe3 — which we designate as a Kane-Mele heterobilayer, as the composition of the layers differs by the N element. From density functional theory calculations and the use of maximally localized Wannier functions, we show that these properties can be controlled by electric fields. The Berry curvature of the heterobilayer reveals a valley quantum Hall signature, and the presence of an electric field can change the Berry curvature sign for specific regions of the Brillouin zone depending on the orientation and intensity of the applied field. The system remains with the topological invariant Z2 = 0, being a trivial band semiconductor regardless of the field strength. The tunable energy gap in the valley region enables manipulation of the valley degree of freedom. A marked anisotropy in the optical conductivity was observed, with the out-of-plane optical absorption shifted to the blue compared to the in-plane absorption, and the electric field altering both the intensities and positions of the absorption peaks.